2018
DOI: 10.1186/s12889-018-5352-6
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of excess body weight and underweight among 26 Chinese ethnic minority children and adolescents in 2014: a cross-sectional observational study

Abstract: BackgroundLittle is known regarding the nutritional burden in Chinese ethnic minority children. This study aimed to investigate the epidemiological characteristics of excess body weight and underweight for 26 ethnic groups.MethodsData on 80,821 participants aged 7–18 years across 26 minorities, with completed records from a large national cross-sectional survey, were obtained from Chinese National Survey on Students’ Constitution and Health (CNSSCH) in 2014. Excess body weight, underweight and their components… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 38 publications
2
26
1
1
Order By: Relevance
“…The current study sample not only came from rural China but also predominantly consisted of ethnic minorities. Previous studies reported ethnicity variations in overweight and obesity among Chinese children and adolescents [ 34 , 35 ]. However, factors associated with the ethnicity variations were not fully examined.…”
Section: Discussionmentioning
confidence: 99%
“…The current study sample not only came from rural China but also predominantly consisted of ethnic minorities. Previous studies reported ethnicity variations in overweight and obesity among Chinese children and adolescents [ 34 , 35 ]. However, factors associated with the ethnicity variations were not fully examined.…”
Section: Discussionmentioning
confidence: 99%
“…33 The speed of shift may be higher in Han nationality than that in ethnic minorities, as many ethnic minorities in China are socioeconomically disadvantaged relative to Han nationality. 8 This is a possible explanation for the results of logistic regression. Previous studies reported a positive correlation between the energy contribution of animal sources to the diet and overweight/obesity whereas plant-based diets are either protective or no association with overweight/obesity in children and adolescents.…”
Section: Discussionmentioning
confidence: 91%
“…6,7 Some scholars proposed that over-nutrition of Han nationality and under-nutrition of ethnic minorities among children and adolescents in China need to be taken seriously. 8 As suggested by previous research and the WHO's report, dietary factors play a crucial role in the development of chronic diseases and obesity. 9,10 Different socioeconomic status, ways of preparing and consuming foods, traditional foods and customs of different ethnic groups in China may cause the differences in their dietary behaviours.…”
Section: Introductionmentioning
confidence: 98%
“…Similar results are shown in the research results [30] in Ethiopia, the height growth can be hampered if a child has a protein deficiency (even though energy consumption is sufficient) for a long period of time. Meanwhile, body weight is more influenced by the lack of energy consumption [30] [31].…”
Section: Efficacy Of Biscuits On Nutritional Statusmentioning
confidence: 99%
“…The rapid growth and loss of passive immunity are in the period from the start of weaning until the age of five, which is a life-prone period. If a child does not get special attention, then the child is prone to nutritional problems [3] [4][5] [6]. Thus, the child should be given care in the form of proper care, especially in the food nutrients.…”
Section: Introductionmentioning
confidence: 99%